ADVERSE EVENTS OF INTERFERONS WITH SYSTEMIC EFFECT - A. A. Toporov; A. S. Kolbin (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Objective: To explore the profile of adverse events associated with interferon therapy. Design: Systematic review. Data sources: Electronic and paper records in subject area from 2000 to 2014. Methods: We searched for the studies on safety and tolerability containing adverse events of interferons with systemic effect. Results: The most frequent adverse events were: flu-like syndrome (55%), depression (30%), neutropenia (20%), anemia (13%). Conclusion: Adverse events are a very serious problem of interferon treatment. System of pharmacovigilance provides forecasting and early identification of these adverse events, as they are predictable.